Controllable Synthesis of Biocompatible Fluorescent Carbon Dots From Cellulose Hydrogel for the Specific Detection of Hg2+ - Huang, Hailong; Ge, Hao; Ren, Zhipeng; Huang, Zhijian; Xu, Min; Wang, Xianghui (Frontiers in Bioengineering and Biotechnology, 2021)
Heavy metal ions overload can seriously harm human health. Simple and effective strategies for the specific detection of heavy metal ions are of great important. In this work, using different pretreatment methods, a series of carbon dots (CDs) with different particle sizes and doped with varying amounts of elements (O, N, S) were prepared based on the natural polymer, cellulose hydrogel. The CDs exhibit excellent fluorescence and biocompatibility. When the particle size decreased from 8.72 nm to 2.11 nm, the fluorescence quantum yield increased from 0.029 to 0.183. In addition, doping with elements (N) also effectively enhanced the fluorescent performance of the CDs. The fluorescence of the CDs, especially for the smallest, CD-4a, was significantly quenched in the presence of the heavy metal ion, Hg2+. Thus, CD-4a may be used as a fluorescence sensor for the detection of Hg2+. The fluorescence intensity of CD-4a exhibited a two-stage, concentration-dependent fluorescence response in the range 0.2-10 and 10-100 μmol/L Hg2+, with each stage having different slopes; the detection limit was 0.2 μM. More importantly, even in the presence of interfering metal ions, the detection of Hg2+ using the CDs-4a remained stable. Therefore, these biocompatible CDs may serve as a promising candidate for the specific detection of Hg2+.